Avaliacão qualitativa de carnes de catetos (tayassu tajacu) e cutias (dasyprocta aguti) criados em cativeiro no semi-arido nordestino - Barbosa, Polyanna Dantas Fernandes de Sousa Freitas (2010)
Eight samples of peccary meat (Tayassu tajacu) and thirteen samples of agouti meat (Dasyprocta agouti) were collected and analysed using physicochemical and microbiological parameter. In the analysis were used 08 peccaries and 13 agoutis, all intensive farming. The meats were tested for moisture, dry matter and minerals; in microbiological analysis searched for the presence of enterobacteria, Staphylococcus and mesophilic bacteria. In the determination of dry matter, the average performance was 26.87 ± 1.1% for agoutis and 29.17 ± 1.54% for peccaries. In the analysis of minerals, we obtained an average of 4.84 ± 0.87 for peccaries and 4.72 ± 0.37 for agoutis. For the determination of moisture, peccary samples showed 70.83% and agouti samples showed 73.13%. In the analysis of enterobacteria, peccary samples had an average of 1.57 log10 UFC/g, and agouti samples had an average of 1.5 log10 UFC/g. In the determination of Staphylococcus, the samples showed an average of 1.57 log10 UFC/g and 1.55 log10 UFC/g for peccaries and agoutis, respectively. For mesophilic bacteria, peccary samples showed an average of 1.72 log10 UFC/g and agouti samples showed an average of 1.77 log10 UFC/g. Therefore, the physicochemical results were satisfactory compared with other animals of the same order. The microbiological results showed low levels of contamination.